EXPLORING THE USE OF ARTIFICIAL INTELLIGENCE IN MOTOR LEARNING IN TENNIS - ION-MUȘAT, Dana (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Sports have always been an important component of human culture due to the combination of neuro-psychic skills, strategic planning, and physical excellence. With the discovery and rapid development of artificial intelligence, its applicability in the sports domain is becoming increasingly evident, and its deep integration is an inevitable trend at this moment. In sports, artificial intelligence combined with data analysis highlights unparalleled opportunities regarding motor learning, outcome prediction, decision-making capabilities, and performance optimization. The integration of methodologies offered by artificial intelligence represents an innovative approach to enhancing athletic performance, which will continue to evolve as a foundation for the technology of sports science. The technique and tactics of tennis have reached a high level due to the evolution of sports equipment, and in response to this phenomenon, coaches have increasingly leveraged the physical training of athletes as it has developed. Following a review of the literature from recent years, we concluded that the data obtained through artificial intelligence provide specific details that can assist coaches and tennis players both in planning training and in the motor learning process. Furthermore, the results obtained through AI in sports analysis, especially for a fast and strategic sport like tennis, have effects on the level of optimization of athletic performance, which implicitly reflects on the competitive results of players. Therefore, this study aims to provide information to tennis coaches and players on how artificial intelligence can be utilized to facilitate motor learning with the objective of optimizing athletic performance. Additionally, we believe that the application of artificial intelligence in the training of tennis players offers specialists insights that can facilitate the adaptation of training methodologies to optimize the motor learning process. By utilizing this information in training, coaches can adapt training methods to meet the demands of modern tennis, thereby improving player outcomes. With technological advancement, the continuous exploration of the motor learning process through artificial intelligence is justified in the attempt to achieve significant or even major progress in optimizing athletic performance in tennis.